Phytoremediation apparatus for heavy metal contaminated sediment using LED and microalgae and phytoremediation method of use thereof - KWON, HYEONG GYU; LEE, SEONG HO; JEON, JIN YOUNG; OH, SEOK JIN (2017)
The present invention provides a phytoremediation apparatus for heavy metal contaminated sediment using a light emitting diode and microalgae. The phytoremediation apparatus includes: a semi-permeable bag capable of having a certain volume and growing microalgae; a sealing clip fixed to both ends or one end of the semi-permeable bag to seal the semi-permeable bag; an LED mounted on one surface of the sealing clip and capable of supplying light inside the semi-permeable bag; and an electricity supply capable of supplying energy to the LED. Thus, the heavy metals are purified in an environmentally friendly manner, and the microalgae absorbing heavy metals or heavy metal attached microalgae is collected such that the microalgae is prevented from being fed to the organisms in an upper nutritive step and is available for industrialization such as bio oil. 본 발명은 본 발명은 일정 부피를 갖고 미세조류를 생장시킬 수 있는 반투막 주머니, 반투막주머니의 양단 또는 일단에 고정되어 반투막주머니를 밀폐시킬 수 있는 실링클립, 실링클립의 일면에 장착되고 반투막주머니 내부에 빛을 공급할 수 있는 LED, LED에 에너지를 공급할 수 있는 전기공급부를 포함하는 것을 특징으로 하는 발광다이오드와 미세조류를 이용한 중금속 오염퇴적물의 식물정화장치를 제공함으로써 친환경적으로 중금속을 정화하고 중금속을 흡수 또는 흡착한 미세조류는 상위영양단계의 생물로 먹이전송이 되지 않게 회수하여 바이오오일 등의 산업화에 이용 가능하도록 한 발광다이오드와 미세조류를 이용한 중금속 오염퇴적물의 식물정화장치를 제공한다.